Animosity and Switching Intention: Moderating Factors in the Decision Making of Chinese Ethnic Diners. (May 2019) - Kim, Jong-Hyeong
In this context of the recent political dispute between China and South Korea, this study examines the influence of the animosity of Chinese ethnic diners. By extending cognitive appraisal theory, this study develops an animosity model that links animosity beliefs, negative emotions, switching intentions, and the moderators of localization and corporate social responsibility (CSR) practices. The results show that animosity beliefs significantly affect switching intention both directly and indirectly through negative emotion. We also find that ethnic restaurants' localization practices and CSR practices to support the local community alleviate the animosity effect on negative emotions associated with dining in an ethnic restaurant that has the cultural theme of the offending country. The results allow ethnic restaurateurs to gain insights into how to develop effective marketing strategies during crisis periods when animosity erupts against the country of origin of their ethnic cuisine.